Environmental values, valuation methods and natural disaster damage assessment - Dosi, Cesare (ECLAC SantiagoCL, 2001)
Illustrates the concept of environmental values from an economic perspective. Provides an overview of valuation methods aimed at quantifying these values in monetary terms. Makes a preliminary attempt to identify a strategy for integrating environmental damages into natural disaster impact assessment.